Revisiting the Role of Bank's Capital, Loan Loss Provisioning and Risky Assets to Credit Risk in Malaysia: An Application of Dynamic Heterogenous Panel Technique - Hishamuddin Abdul Wahab (Academic Research Publishing Group, 2024)
Indexed by Scopus